Systemic Transformation Readiness of Arabic Language Education in Indonesia: Structural Gaps and Reform Imperatives - Kartini; Naidin Syamsuddin; Muhammad Irfan Hasanuddin; M. Ilham (TARBIYA: Journal of Education in Muslim Society, 2026)
Abstract This study examines the readiness of Arabic language education in Indonesia for systemic transformation amid technological, sociocultural, and employment-related disruption. It asks how the system can be redesigned to remain relevant, adaptive, and responsive to contemporary academic and professional needs. Using a qualitative systemic-analysis design, the study analyzed 30 documents comprising 10 national policy and regulatory documents and 20 peer-reviewed scholarly publications. Data were coded through a structured document-analysis protocol and examined using policy mapping, qualitative content analysis, and systemic synthesis. The findings indicate uneven readiness across seven analytical domains. Policy and governance frameworks show the strongest reform momentum, whereas curriculum flexibility, pedagogical innovation, teacher capacity, assessment reform, and learner competency alignment remain moderate to low. The most persistent weakness is the dominance of a religious-textual orientation without sufficient integration of communicative, functional, and professional competencies. The study proposes a six-layer transformation framework connecting epistemological reorientation, curriculum redesign, pedagogical innovation, teacher capacity development, governance coordination, and competency-based assessment. The framework offers a conceptual basis for coordinated policy and institutional reform, although its effectiveness requires empirical validation in classrooms and institutions. Abstrak Penelitian ini mengkaji kesiapan pendidikan bahasa Arab di Indonesia untuk melakukan transformasi sistemik di tengah disrupsi teknologi, perubahan sosiokultural, dan tuntutan dunia kerja. Penelitian ini menelaah bagaimana sistem pendidikan bahasa Arab dapat dirancang ulang agar tetap relevan, adaptif, dan responsif terhadap kebutuhan akademik serta profesional kontemporer. Dengan menggunakan desain analisis sistemik kualitatif, penelitian ini menganalisis 30 dokumen yang terdiri atas 10 dokumen kebijakan dan regulasi nasional serta 20 publikasi ilmiah yang ditelaah. Data dikodekan melalui protokol analisis dokumen terstruktur, kemudian dianalisis menggunakan pemetaan kebijakan, analisis isi kualitatif, dan sintesis sistemik. Temuan menunjukkan kesiapan yang tidak merata pada tujuh domain analitis. Kerangka kebijakan dan tata kelola menunjukkan momentum reformasi yang paling kuat, sedangkan fleksibilitas kurikulum, inovasi pedagogis, kapasitas guru, reformasi penilaian, dan keselarasan kompetensi peserta didik masih berada pada tingkat sedang hingga rendah. Kelemahan yang paling persisten ialah dominasi orientasi keagamaan-tekstual tanpa integrasi yang memadai dengan kompetensi komunikatif, fungsional, dan profesional. Penelitian ini mengusulkan kerangka transformasi enam lapisan yang menghubungkan reorientasi epistemologis, perancangan ulang kurikulum, inovasi pedagogis, pengembangan kapasitas guru, koordinasi tata kelola, dan penilaian berbasis kompetensi. Kerangka ini menyediakan landasan konseptual bagi reformasi kebijakan dan kelembagaan yang terkoordinasi, tetapi efektivitasnya masih memerlukan validasi empiris di kelas dan institusi.